1988
DOI: 10.1152/ajpendo.1988.254.4.e532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the isotopic equilibration between lactate and pyruvate

Abstract: When an isotopic tracer is infused for the purpose of determining the rate of turnover or oxidation of a substrate, it is assumed that the resulting isotopic enrichment by the tracer will reflect the kinetics of only the pool of interest. However, this may not be the case when carbon-labeled lactate is infused, since rapid isotopic exchange with the intracellular pyruvate and alanine pools could potentially occur. Therefore we have determined the extent of isotopic exchange occurring during the infusion of [3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 7 publications
1
49
0
Order By: Relevance
“…3, A and B). In vivo, lactate rapidly equilibrates across LDH, making accurate determinations of lactate turnover via tracer infusion more challenging (29). Nevertheless, the individual and overall differences between glycerol and lactate turnover rates identify a substantial shift to a PEPCK-independent gluconeogenic precursor at a rate that can account for a third of EGP (Fig.…”
Section: Pepck-m Deficiency Promotes a Gluconeogenic Substrate Switchmentioning
confidence: 99%
“…3, A and B). In vivo, lactate rapidly equilibrates across LDH, making accurate determinations of lactate turnover via tracer infusion more challenging (29). Nevertheless, the individual and overall differences between glycerol and lactate turnover rates identify a substantial shift to a PEPCK-independent gluconeogenic precursor at a rate that can account for a third of EGP (Fig.…”
Section: Pepck-m Deficiency Promotes a Gluconeogenic Substrate Switchmentioning
confidence: 99%
“…These effects are largely due to monocarboxylate metabolism in the lungs. Hence, assertions that the IEs of lactate and pyruvate are equivalent in mammalian blood following tracer infusion (27) are simply incorrect. In brief, the present results show that the lungs metabolize substrates delivered in the pulmonary artery and, further, that lung metabolism affects metabolite concentrations and isotopic enrichments when tracers are infused into the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the increased rate of G-6-P neogenesis (4 -8 mol of C6 unit ⅐ kg Ϫ1 ⅐ min Ϫ1 ) exceeded M-HGR (0.9 mol ⅐ kg Ϫ1 ⅐ min Ϫ1 ), which indicated that the suppression of M-HGR by GPI treatment was associated with abolished net glycogenolysis and also redirected G-6-P flux from glucose release toward other pathway(s), such as glycogen synthesis and glycolysis. In addition, with GPI treatment, there was a shift of net hepatic lactate balance from production to uptake, and with a rapid equilibration between the plasma lactate pool and the intracellular lactate and pyruvate pools (Wolfe et al, 1988), this shift in lactate balance may have reflected a shift from pyruvate generation to pyruvate consumption in the net sense. Intracellular pyruvate is generated by glycolysis and deamination of amino acids mediated by transaminases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in dogs and humans have shown that increased delivery of gluconeogenic precursors, such as alanine (Diamond et al, 1988;Wolfe et al, 1988), glycerol (Jahoor et al, 1990), or lactate (Jenssen et al, 1990;Connolly et al, 1993), to the liver has no acute effect on the amount of glucose produced by that organ. Gluconeogenic precursors can alter hepatic glycogen metabolism by exerting regulatory effects on glycogen phosphorylase and synthase in addition to serving as substrates for glycogen synthesis (Youn and Bergman, 1990), of which glucose 6-phosphate (G-6-P), an intermediate at a central cross point between the metabolic pathways of glycogen metabolism and gluconeogenesis, has been shown in studies using isolated hepatocytes to regulate glycogen synthase (Ciudad et al, 1986) and phosphorylase activity within a physiological range (Aiston et al, 2003(Aiston et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%